2017
DOI: 10.1186/s41239-017-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Technologically-mediated communication: student expectations and experiences in a FOMO society

Abstract: While technology enables a wider section of society to access higher education, accessing, as a process, fundamentally differs from acquiring the individual and systemic skills required for online learning. This study presents primary data about perceptions of, and experiences with, online learning in an Australian university from a survey of 289 distance education (DE) students. Epistemologically, it prioritises giving agency and voice to an increasingly disempowered collective, online learners, who often are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
10
0
5
Order By: Relevance
“…Interestingly, all participants but one spontaneously used on-campus study as a reference point when sharing their experiences and perceptions related to online learning. Providers and educators that use campus-based learning as a reference point when presenting resources and opportunities in online learning may be contributing to unrealistic expectations of online learning and the fear of missing out on-campus-based learning (Ragusa 2017). The findings from the present study support previous research that revealed the opportunities and challenges of online learning compared to on-campus study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, all participants but one spontaneously used on-campus study as a reference point when sharing their experiences and perceptions related to online learning. Providers and educators that use campus-based learning as a reference point when presenting resources and opportunities in online learning may be contributing to unrealistic expectations of online learning and the fear of missing out on-campus-based learning (Ragusa 2017). The findings from the present study support previous research that revealed the opportunities and challenges of online learning compared to on-campus study.…”
Section: Discussionsupporting
confidence: 74%
“…;Yanuschik et al 2015;Mayer 2018). While the popularity of online learning can be attributed to the flexibility inherent to its medium, research has identified concerns related to student engagement (Prior et al 2016), retention rates (Mubarak et al 2020;Jo et al 2015), and reported perceptions of missing out on traditional classroom experiences (Ragusa 2017;Martinez et al 2020). Current trends indicate that a greater proportion of students engage in online learning than in the past (Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Campus-based lectures and seminars are assessed as more dynamic/involving what again, according to the interviewed students, facilitates learning. Ragusa (2017) -Technologically-mediated communication: student expectations and experiences in a FOMO society,‖ discusses results of the students' survey on distance education (DE) at Australian University. One of the findings points out to the fact that, -Regardless of the convenience (…) electronic communication permitted, DE [distance education] students simply failed to believe interactive online platforms were a suitable substitute for ‗real' human interactions.…”
Section: Summary Of the Research Findings And Discussionmentioning
confidence: 99%
“…One of the findings points out to the fact that, -Regardless of the convenience (…) electronic communication permitted, DE [distance education] students simply failed to believe interactive online platforms were a suitable substitute for ‗real' human interactions. Face-to-face interactions, unlike TMC [technologically-mediated communication], were perceived motivational and thus crucial for academic learning‖ (Ragusa, 2017). With regard to online phase, the students appreciate the fact that they can work at their own pace (e.g., Ragusa, 2017).…”
Section: Summary Of the Research Findings And Discussionmentioning
confidence: 99%
See 1 more Smart Citation